Effects of a program for the development of emotional skills in university students - Luy-Montejo, Carlos Augusto (2020)
The objective of this study was to evaluate the effects of the program I discover my potentialities in a group of first cycle university students; the study design was preexperimental, it worked with a sample of 382 students from the business, engineering and humanities areas, of both sexes and from national and private schools; BarOn's ICE emotional intelligence inventory was used for pre and post measurement. Significant differences were found between the pre and post after applying the PRODPE, which shows that the program achieved the development of emotional skills.